Defining compromise area in the processes of multimodal delivery organization within the agile approach - Berestenko, Viktor; Onyshсhenko Svitlana (Eastern-European Journal of Enterprise Technologies, 2024)
The level of competition in the transport market requires delivery organizers to implement better approaches based on modern management methodologies, in particular, agile, which makes it possible to provide a modern level of service to cargo owners. The object of this research is the processes of organizing multimodal delivery. The subject of the study is the area of compromise in the processes of organizing multimodal delivery based on the agile approach. The term «compromise area» is introduced, which reflects the numerical limits of product parameters in the general case. For the transportation domain under consideration, the «trade-off area» reflects the limits of the characteristics of multimodal delivery, which is the «product» for the multimodal operator. A set of alternative options for multimodal delivery forms the basis for establishing the dependence of the cost of delivery on time and its reliability (possible time deviation). The area in the «time-reliability-cost» space, which is formed on the basis of this dependence, on the one hand, and the requirements of the cargo owner, taking into account their possible adjustment, on the other hand, is the area of compromise. This area is proposed for use in agile approaches to the organization of multimodal delivery. Balancing the interests of the cargo owner and the multimodal operator allows changing the limits of the compromise area within the framework of the proposed scheme of agile cycles in the process of planning and organizing delivery. On the example of delivering a container with cargo from China to Kyiv, regression linear models were built. These models formalize the dependence of delivery cost on reliability and/or time. Using the example of varying the requirements of the cargo owner regarding the limitations of some delivery characteristics, the formation of the compromise area and its adjustment was carried out, which demonstrated the practical aspects of the formation of the compromise area for multimodal delivery. The results are the basis for the implementation of the agile approach in the field of multimodal transportation. The further development of these results consists in the construction of mathematical models that could form the basis for finding solutions in the area of compromise